Enhancing Efficiency and Scalability: DevOps Implementation for Educational Chat Systems - Meghana, N; Sri Lakshmi, K; Naga Lakshmi Teja Sree, M; Srujana, K; Ashok, N (International Journal of Computer Sciences and Engineering, 2024)
This study presents a thorough technique for the implementation of a Telegram chatbot created especially for educational institutions to expedite the tracking of attendance and academic results. The chatbot is constructed using Python`s Telebot library and DevOps concepts. It is then carefully deployed on an AWS EC2 instance to ensure smooth interaction with a variety of educational systems and to meet the specific needs of different academic institutions. Jenkins makes continuous integration easier by automating the deployment and build processes, which increases scalability and efficiency. The chatbot`s customization possibilities enable customized integration with current educational infrastructures, guaranteeing flexibility and adaptability. Additionally, the project`s strong design allows for future growth and the addition of sophisticated features like learning management system integration. The chatbot seeks to maintain ongoing relevance and efficacy in promoting student participation and optimizing academic administration procedures by continuing to be flexible in response to new technological developments. This study demonstrates how chatbot technology may revolutionize educational services and administration, supporting the further development of academic institutions in the digital era. This study highlights the revolutionary potential of chatbot technology in transforming student services and academic administration by connecting technological innovation with educational demands.